2017
DOI: 10.1016/j.ijpharm.2017.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of multi-walled carbon nanotube-liposome drug delivery platforms

Abstract: The aim of this study is to design and develop delivery platforms made of liposomes and multi-walled carbon nanotubes (MWCNTs). We used different lipids with different main transition temperature (Tm) and differently functionalized MWCNTs with organic addends possessing either positive or negative charge. The phospholipids used for the formulations were 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) (Tm=41°C) and L-α-phosphatidylcholine, hydrogenated Soy (HSPC) (Tm=53°C). By Differential Scanning Calorimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Studies have shown that MWCNT is a suitable carrier for poorly soluble drugs (24,38). On the one hand, the current study developed the application range of MWCNTs in the field of pharmacy, on the other hand, it attempted to develop a new platform for the delivery of poorly soluble drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that MWCNT is a suitable carrier for poorly soluble drugs (24,38). On the one hand, the current study developed the application range of MWCNTs in the field of pharmacy, on the other hand, it attempted to develop a new platform for the delivery of poorly soluble drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Although MWCNTs have been recently used for loading other drugs, they have not been studied as drug delivery systems for DDM (2123). Multiple studies have proposed carriers, including MWCNTs, with delineation of pore volume, surface area and surface modification (2426). Among the many factors that play a role in the process of drug delivery, drug-loading efficiency is particularly critical for MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have attracted great interest for biomedical applications, including the delivery of bioactive molecules such as drugs, the targeted cancer therapy, and biological imaging, because of their unique properties, including large surface area, relatively low density, high stability and other inherent mechanical, optical and electrical properties [7][8][9]. CNTs can be produced as single-walled CNTs (SWCNTs) or multi-walled CNTs (MWCNTs) [10]. SWCNTs can be easily synthesized and efficaciously traverse biological barriers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Carbon nanotubes (CNTs) are carbon allotropes with different length and diameter cylindrical nanostructure with amazing mechanical, electrical, thermal, and adsorption properties. [15][16][17][18] Versatile outstanding applications of CNTs were used in many industrial sectors and on industrial scale such as lithium ion battery, 19 drug delivery system, 20 biomedical applications, 21 and manufactured implants. 22 In particular, CNTs have many applications in electronics like implantable supercapacitors, 5 field effect transistors, 23 and photovoltaics.…”
Section: Introductionmentioning
confidence: 99%